ANALISIS POTENSI PEMANFAATAN KAWASAN PULAU LAIN DAN PULAU HATALA NEGERI ASSILULU, KABUPATEN MALUKU TENGAH - Muhammad Z. U. Payapo; Fajar Hermawan; Musa Karepesina; Lidya Katili; Abdul A. Usemahu; Syarifudin A. Kilbaren; Kedswin G. Hehanussa (Amanisal: Jurnal Teknologi dan Manajemen Perikanan Tangkap, 2025)
This research aims to identify the potential and forms of utilization in the Lain Island and Hatala Island areas, analyze potential problems in the utilization activities of the Lain Island and Hatala Island areas, and determine management and utilization strategies. This research was conducted from July to August 2019 on Lain Island and Hatala Island, Negeri Asilulu, Leihitu District, Central Maluku Regency. The potential and forms of utilization and problems due to utilization activities were analyzed descriptively qualitatively through data from direct observation and interviews and participatory mapping to describe the potential and forms of utilization of Lain Island and Hatala Island with the ArcGis 10.3 program. Analysis of management strategies for Lain Island and Hatala Island was carried out using the DPSIR method. The results of this study show that the potential found in the Lain Island and Hatala Island area includes small islands with an island area of less than 2,000 km2, has a main ecosystem of coral reefs with the type (fringiing reef) and also fishery resources consisting of fish and non-fish resources. while the forms of utilization found are in the form of fishing areas, boat moorings and longboat landings ± about 128 meters parallel to the coastline, residential areas which are ± 0.115 ha on Lain Island and agricultural land.